Study of BMI in pregnancy and its correlation with maternal and perinatal outcome - Choudhary, Jaya; Singh, Swati; Tiwari, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal nutrition plays an important role in maternal and fetal outcome. The low maternal BMI or Obesity is associated with adverse outcome. Methods: A total 148 primigravida included. BMI was calculated on first visit and in each trimester, all booked patient was followed throughout pregnancy and delivery for any maternal and fetal complications. Results: (66.2%) of patients were with normal BMI, (17.56%) were underweight, (10.13%) were overweight and (6.08%) patients were obese. APH was seen in (11.1%) and (6.7%) cases in BMI grades ‘IV and III’ respectively. PIH was present in total 10 cases, (33.3%) cases belonged to BMI grades IV. Anemia was present in total 51 cases (53.8%) belonged to BMI grade I. Preterm delivery was present in total 5 cases and out of them (7.7%), (2%) and (11.1%) belonged to BMI grades I, II and IV respectively. GDM was present in 11 cases and out of them (26.7%) and (44.4%) cases belonged to BMI grade III and IV respectively. PPH was present in total 5 cases and out of them (7.7%), (2%) and (11.1%) belonged to BMI grades I, II and IV respectively. In BMI grade I group, (96.2%) babies had birth weight <2.5, while in BMI grade IV, (88.9%) babies had birth weight >2.5 (22.2%) cases of fetal macrosomia belonged to BMI grade IV. Conclusions: There is importance of pr-pregnancy counseling in maintaining weight of women during pregnancy to avoid pregnancy maternal and fetal outcomes.